Research on the evolution mechanism of shale mechanical properties under variable bedding angles - Du, Feng; Liang, Bing; Wen, Xiaoyong; Liu, Qian; Ma, Junxiu; Ren, Yixing; Zhang, Mi; Liu, Jihan; Tan, Jin (Frontiers in Earth Science, 2025)
Mechanical properties are significantly influenced by highly developed bedding planes in shales. This leads to incorrect prediction of fracturing parameters, which results in inefficient fracturing reconstruction of shale reservoir. Therefore, it is of great significance to investigate the effect of bedding planes on the mechanical properties of shales and the mechanism of fracturing efficiency. In this paper, uniaxial compression experiments under variable bedding angles are carried out based on the outcrop shale of the Longmaxi Formation in Sichuan, China. Thereafter, the Aramis system is employed to examine the deterioration process and morphology of the specimens, and the Mechanical properties obtained are utilized to investigate the mechanisms through which the bedding plane influences the hydraulic fracturing stimulation. The findings of the study indicate that the compressive strength and modulus of elasticity of the specimens initially decrease and then increase with an increase in bedding angle. When the bedding angle at the range of 0°–15°, the predominant failure mode observed in the specimens is a mixed failure involving tension and shear, which penetrates the bedding plane. The failure mode observed in the specimen, with a bedding angle of 30°–60°, is predominantly shear failure along the bedding plane. In specimens subjected to a bedding angle of 75°–90°, failure modes are typically tensile failure parallel to the bedding plane and shear failure along the bedding plane. During hydraulic fracturing, the initial expansion of fractures occurs in a direction perpendicular to the minimum horizontal principal stress. In the event that the model contains bedding planes, the hydraulic fracture tends to expand along the bedding plane following an intersection with the plane. This phenomenon serves to promote a significant extension of the hydraulic fracture. Furthermore, the model incorporating bedding planes exhibits reduced apertures of hydraulic fractures and diminished pressures during the propagation stage of the fractures in comparison to the base model. The research results contribute to a comprehensive understanding of the evolutionary mechanisms governing the mechanical properties of shale reservoirs, as well as the expansion patterns of fractures under hydraulic fracturing stimulation.